A case study of New Mexico middle schools: implications for school language policy formation - Anaya, Paul Carlos (Kansas State University, 2006)
This was a case study of two middle schools in New Mexico. Using organization for instruction (Marks and Louis, 1997) as a crux, the purpose of the building level study was to explore the elements of school leadership, instruction, and middle level program and to infer aspects of language policy. The needs threshold was based on the timeliness of reexamining linguistic diversity and on the importance of language concerns in education, principally as they related to ELLs and other linguistically diverse students. The problem stemmed from dynamic, culturally evolving changes in the environment of the two middle schools under study. Changes from economic factors, district leadership, immigration, and demographic shifts in the local area affected the two buildings’ capacity to effectively deliver educational and language services. The significance of the study maintained that school level language planning was rapidly becoming a competing theme in the process of education and required attention in light of important environmental and sociological factors. Metaphor was employed to help symbolize increasing complexities (e.g., array of special interests, human and individual diversity, etc.) found in context of the school with reference to organization, leadership, instruction, and program. Since the research was a case study, no hypotheses were formulated; instead a major research question and four sub questions were posed. A mixed method, multiple sources of information methodology was used in the collection and analysis of data. Twenty (N = 20) participants made up of building leaders (n = 4) and teachers (n = 16) were interviewed. Tables of student achievement scores were presented along with other demographic data. Although interviewees reported sensitivity to linguistic diversity, findings pointed to a lack of knowledge about language policy at all levels on the part of building leaders and teachers. Implications drawn described the important role language policy formation could play in educational structuring of middle school programs and instruction. A list of recommendations provided criteria to follow in making decisions about the feasibility of conducting school level language planning and made suggestions for further research. An extensive bibliography of relevant sources and transcripts of interviews were provided.
Keywords: ELLs; School Language Policy; Middle Schools; New Mexico; Linguistic Diversity; Linguistically divese students; Education, General (0515)